2014
DOI: 10.1161/atvbaha.114.304015
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque, Intima-Media Thickness, and Incident Aortic Stenosis

Abstract: Objective-Aortic stenosis (AS) shares risk factors with atherosclerotic vascular disease. Carotid intima-media thickness (IMT) and plaque may reflect the cumulative damage from exposure to different atherosclerotic risk factors. We examined the relationship of carotid IMT and plaque with incident AS in a prospective population-based study. Approach and Results-A random sample of participants (age, 45-68 years) in the population-based Malmö Diet and Cancer Study underwent B-mode ultrasound with measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…That study did not adjust for BMI, which was a strong confounder of the association between T2DM and aortic valve stenosis in our study, and a risk factor for aortic valve stenosis [17]. In two smaller prospective studies, DM was associated with an approximately 3-fold increased risk of aortic valve stenosis in a cohort of 5079 Swedish adults (including 69 cases in the whole cohort) [18] but was not associated with risk of aortic valve stenosis in a cohort of 3243 Norwegian adults, possibly because of lack of power with only 6 cases among DM patients [19]. None of the above mentioned reports specified the type of DM.…”
Section: Discussionmentioning
confidence: 63%
“…That study did not adjust for BMI, which was a strong confounder of the association between T2DM and aortic valve stenosis in our study, and a risk factor for aortic valve stenosis [17]. In two smaller prospective studies, DM was associated with an approximately 3-fold increased risk of aortic valve stenosis in a cohort of 5079 Swedish adults (including 69 cases in the whole cohort) [18] but was not associated with risk of aortic valve stenosis in a cohort of 3243 Norwegian adults, possibly because of lack of power with only 6 cases among DM patients [19]. None of the above mentioned reports specified the type of DM.…”
Section: Discussionmentioning
confidence: 63%
“…14 Because AS shares risk factors with AMI and HF, 4,[15][16][17][18] possible benefits from the widespread use of several cardiovascular pharmacotherapies and lifestyle improvements may also extend to AS. However, large studies investigating the temporal trends of incidence and mortality of AS in the population are lacking.…”
Section: Editorial See P 969 Clinical Perspective On P 994mentioning
confidence: 99%
“…Further support for this concept comes from observations that age-related valve degeneration is characterized by inflammation and foam cell deposition in the valve tissues and angiotensin II activity, processes that are similar to atherosclerosis and that are associated with atherosclerotic disease in other vascular territories. [15][16][17]31,32 Risk factors for AS are similar to risk factors for coronary artery disease, stroke, and peripheral vascular disease and include high low-density lipoprotein cholesterol, smoking, and diabetes mellitus. [15][16][17] Recent genetic and experimental studies provide additional evidence that the disease might be preventable with lipid-modifying medications, angiotensin receptor blockers, and ACE inhibitors.…”
Section: Patient Characteristics and Incidencementioning
confidence: 99%
“…[124] (Table 1) This finding has subsequently been confirmed in independent Canadian and Danish cohorts[125, 126] and reinforces the hypothesis that the process of valvular age-related degeneration shares key pathophysiologic features with that observed in atherosclerotic vessels. [127129] In a second analysis of the same cohorts, it was further shown that a polygenic score comprised of alleles associated with increased LDL cholesterol also conferred increased risk of aortic valve calcium and stenosis, providing further support for a role of blood lipids beyond lipoprotein(a) in the development of calcific aortic valve disease. [130]…”
Section: Cardiac Valvular Phenotypesmentioning
confidence: 99%